Endometriosis as a cause of chronic pain and deterioration of women's quality of life - etiology, symptoms and treatment method - Wilk, Bernadetta; Stachura, Piotr; Witkowska, Edyta; Ciechański, Marcin; Cholewiński, Szymon; Wilk, Klaudia; Rejman, Piotr; Jurkiewicz, Katarzyna; Kasprzyk, Aleksandra; Pszczoła, Katarzyna (Quality in Sport, 2025)
Introduction, purpose Endometriosis is a chronic inflammatory condition that primarily affects pelvic tissues, including the ovaries, and is the most common cause of chronic pelvic pain, significantly impacting the quality of life of women of reproductive age. It is currently estimated that up to 10% of women may be affected by this condition. However, diagnosing endometriosis is challenging and often delayed due to frequent misdiagnoses as well as the relatively common occurrence of asymptomatic cases. Several factors may contribute to the development of endometriosis, including anatomical, genetic, and immunological factors. Additionally, it is believed that diet and lifestyle may influence the course of the disease. It is important to remember that beyond reducing overall quality of life and causing chronic pain, endometriosis may also contribute to the development of depressive and anxiety disorders, making it an interdisciplinary health issue. Materials and methods A systematic literature review was conducted using the PubMed database to explore the current state of knowledge regarding endometriosis, with particular focus on its etiological factors, clinical manifestations, and treatment options. Conclusions Endometriosis remains a mystery and a challenge for modern medicine. There are various theories explaining the etiology of endometriosis; however, none of them is universal, nor do they fully account for the development of the disease in every case. In addition to medications and invasive treatment methods, one must not forget the beneficial impact of a proper diet and an active lifestyle on the progression of the disease and the alleviation of its burdensome symptoms. Patients struggling with this condition should be provided with comprehensive, interdisciplinary medical care.